Ocular pain and discomfort after advanced surface ablation: an ignored complaint - Sobas EM (Dove Medical Press, 2015)
Eva M Sobas,1 Sebastián Videla,2,3 Miguel J Maldonado,1 Jose C Pastor1,4 1Instituto Universitario de Oftalmobiologia Aplicada (IOBA), Universidad de Valladolid, Valladolid, Spain; 2Laboratorios Dr Esteve S.A., Barcelona, Spain; 3Department of Experimental and Health Sciences, Faculty of Health and Life Sciences, Universitat Pompeu Fabra, Barcelona, Spain; 4Department of Ophthalmology, Hospital Clinico Universitario, Valladolid, Spain Purpose: Laser vision correction is one of the most commonly performed elective surgical procedures in ophthalmology. Generally, discomfort besides pain (photophobia, burning sensation, tearing, and foreign body sensation) after these procedures is not taken into consideration in the clinical practice. The objective is to provide data on these symptoms and their relevance after advanced surface ablation (ASA). Methods: Single-center survey study based on a structured questionnaire relative to the patients’ perceived symptoms after ASA. Inclusion criteria were: ≥18 years old, no ocular disease, with myopia (0.75 to 9 D) or hyperopia (0.25 to 5 D) with or without astigmatism, receiving ASA on at least one eye. All procedures were performed by the same surgeon. A descriptive analysis was performed. Results: Seventy-three consecutive patients (34 men and 39 women) were included in the study. The median (range) of age was 33 (19–64) years. Sixty-nine patients had surgery done on both eyes. Postoperative pain was the most frequent comorbidity (97% [95% confidence interval CI: 90–100]) with a median (range) of intensity (verbal numerical rating scale) score of 7 (2–10). Photophobia: 85% (95% CI: 75–92); burning sensation: 62% (95% CI: 50–73); tearing: 59% (95% CI: 47–70); and foreign body sensation: 48% (95% CI: 36–60) were also prevalent postoperative symptoms. Pain during ASA was reported for 44% (95% CI: 32–56) of patients.Conclusion: Comorbidities such as pain, photophobia, burning sensation, tearing, and foreign body sensation are prevalent after ASA procedure. Postoperative pain should be taken into consideration due to its prevalence and intensity. A new and more efficient postoperative analgesic protocol should be established. Keywords: pain, photophobia, refractive surgery, survey